Variability in linseed (Linum usitatissimum) germplasm collections from peninsular India with special reference to seed traits and fatty acid composition - SIVARAJ, N; SUNIL, N; PANDRAVADA, S R; KAMALA, V; ABRAHAM, BABU; KUMAR, VINOD; RAO, B V S K; PRASAD, R B N; VARAPRASAD, K S (The Indian Journal of Agricultural Sciences, 2012)
Eighty-four accessions of linseed (Linum usitatissimum L.) collected from Andhra Pradesh and Maharashtra, were analyzed for seed traits, oil content and fatty acid composition. Field observations on floral and other morphological traits were recorded. Variability was observed in all the agro-morphological and biochemical traits studied. DIVA-GIS software was used to assess the diversity of linseed fatty acid composition for the first time in India. The oil content of the linseed germplasm ranged between 29.4% and 42.6%. IC564681 recorded the highest oil content (42.6%), while the accession IC564591 recorded the least (29.4%). With respect to linolenic acid (omega-3 fatty acid), IC 564631 possessed the maximum (57.1%) and IC564687 the minimum (39.5%). Linseed germplasm with high oleic acid content was identified with IC564627 recording the maximum of 32%. Based on DIVA-GIS diversity analysis for omega-3 profile and test weight of seed, it was inferred that Kohir, Jarasangham, Nayalkal, Shankarampet and Zaheerabad which are sub-units (mandals) of Medak district and Jainoor, Koutala and Bhimni mandals of Adilabad district are potential areas for collection of diverse accessions.